Unilateral Glenoid Hypoplasia: A Case Report and Review of the Literature - Ashish Suryawanshi; Amber Mittal; Snehal Dongre; Neeti Kashyap (Case Reports in Orthopedics)
Glenoid hypoplasia is a relatively rare alteration that in most cases involves the pectoral girdle in a bilateral and symmetrical manner. In general, glenoid hypoplasia is associated with skeletal changes such as hypoplasia of the humeral head or changes in the morphology of the acromion and of the coracoid. We describe a rare case of unilateral glenoid hypoplasia without instability and not involving humeral head. The patient was managed effectively with nonoperative measures that featured specific rehabilitation exercises for the shoulder.